Effect of post-curing light exposure time on the physico–mechanical properties and cytotoxicity of 3D-printed denture base material. Issue 1 (January 2022) - Aati, Sultan; Akram, Zohaib; Shrestha, Barsha; Patel, Jainish; Shih, Benjamin; Shearston, Kate; Ngo, Hien; Fawzy, Amr
Highlights: Effect of post-curing time on 3D-printed denture base material was investigated. Variations in physico-mechanical properties and cytotoxicity were characterized. Physico-mechanical properties were improved with the increase in post-curing time. Fibroblast cell viability was improved with the increase in post-curing time. Post-cured with light exposure for 20 min was most significant. Graphical Abstract: ga1 Abstract: Objective: This study investigated the effect of post curing light exposure time on the physico-mechanical properties and cytotoxicity of a 3D-printed PMMA-based denture material in comparison to a conventional heat-cured alternative as a control. Methods: 3D-printed specimens were fabricated followed by post-curing for 0, 5, 10 or 20 min at 200 W and light wavelength range of 390–540 nm. Heat-cured specimens were fabricated using a standard protocol. Specimens were placed in artificial saliva at 37 ℃ for 48 h (immediate groups) and 6 months (aged group), then evaluated flexural strength/modulus, fracture toughness, microhardness, and degree of conversion. Water sorption and solubility was assessed after 28 days. Flexural strength, flexural modulus, and fracture toughness were tested through three-point bending tests, while the surface hardness was tested using Vickers's test. Fractured specimens were viewed by scanning electron microscope (SEM). Cytotoxicity in term of cell viability was evaluated using human oral fibroblasts. Results: Flexural strength/modulus, fracture toughness and surface hardness significantly improved with the increase in light curing time up to 20 min. The same pattern of improvement was found with degree of conversion, water sorption, solubility, and cell viability. There was no significant difference (p  <  0.01) between heat-cured material and 3D specimens post-cured for 20 min in term of flexural strength/modulus, surface hardness, and degree of conversion at the two-storage time points. Significance: Generally, the physico-mechanical properties of the 3D-printed denture base material improve as post curing time increases up to 20 min which exhibited comparable performance as the conventional heat-cured control.